Pengembangan Handout Elektronik Menggunakan Flip PDF Professional pada Materi Kingdom Plantae sebagai Bahan Ajar Kelas X SMA/MA - Latifah Turrohmah; Nasrul Hakim (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2022)
In the teaching and learning process, teachers often teach using printed books, modules, worksheets, using LCD projectors, and have never combined printed teaching materials with electronic media. Based on the needs analysis questionnaire data given to students of class X MIA at SMAN 6 Metro, as many as 63.3% who have difficulty learning the material Kingdom Plantae. Thus, innovation is needed in the form of electronic handout teaching materials. This study aims to develop Electronic Handouts using Flip PDF Professional on Kingdom Plantae Materials as Teaching Materials for Class X SMA/MA. This type of research is an R&D (Research and Development) research with the ADDIE model which consists of five stages, namely Analysis-Design-Development-Implementation-Evaluate. The final result of Electronic Handout validation using Flip PDF Professional on Kingdom Plantae Materials as Teaching Materials for Class X SMA/MA obtained a percentage of 85.3% in the